An Analysis of Convenience, Trust, and Security of E-Wallet through Understanding Technology as an Intervening Variable - Rosdiana, Monica; Supardi; Indayani, Lilik; Febriansah, Rizky Eka (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aims to analyze the convenience, trust, and security in the decisions to use electronic wallets (Shopee Pay), understanding technology as an intervening variable. The study adopts a quantitative approach, collecting data through questionnaires. The research sample comprises 100 Shopee Pay users in Sidoarjo Regency, selected through purposive sampling. Data analysis involves hypothesis testing and processing using SPSS v.25. Findings indicate that convenience, trust, and security, mediated by an understanding of technology, significantly influence the decision to use E-Wallet (Shopee Pay). The study concludes that convenience, trust, and security, through an understanding of technology, significantly impact the decision to use E-Wallet (Shopee Pay). This research is urgently needed due to the rapid growth of electronic wallet usage in the current digital era. Understanding the factors influencing the decision to use E-Wallets (Shopee Pay) provides valuable insights for companies and payment service providers to enhance user experience and strengthen operational sustainability in an increasingly competitive market. Additionally, understanding technology as an intervening variable provides additional insights into consumer behavior related to financial technology usage. Therefore, this research contributes academically and has significant practical relevance for the industry and stakeholders.